Gene-agnostic approaches to treating inherited retinal degenerations - Chew, Lindsey A.; Iannaccone, Alessandro (Frontiers in Cell and Developmental Biology, 2023)
Most patients with inherited retinal degenerations (IRDs) have been waiting for treatments that are “just around the corner” for decades, with only a handful of seminal breakthroughs happening in recent years. Highlighting the difficulties in the quest for curative therapeutics, Luxturna required sixteen years of development before finally obtaining U.S. Food and Drug Administration (FDA) approval and its international equivalents. IRDs are both genetically and phenotypically very heterogeneous. While this offers many opportunities for gene-by-gene precision medicine-based approaches, this is also a very significant challenge. For this reason, alternative (or parallel) strategies to identify more comprehensive, across-the-board therapeutics for the genetically and phenotypically diverse IRD patient population are very appealing. In addition, even when gene-specific approaches may be available and become approved for use, many patients may have reached a disease stage whereby these approaches may no longer be viable. Thus, alternate visual preservation or restoration therapeutic approaches are needed at these stages. In this review, we underscore several gene-agnostic approaches that are being developed as therapeutics for IRDs. From retinal supplementation to stem cell transplantation, optogenetic therapy and retinal prosthetics, these strategies would bypass at least in part the need for treating every individual gene or mutation or provide an invaluable complement to them. By considering the diverse patient population and treatment strategies suited for different stages and patterns of retinal degeneration, gene agnostic approaches are very well poised to impact favorably outcomes and prognosis for IRD patients.